HUBUNGAN POSTUR, DURASI DAN FREKUENSI KERJA DENGAN KELUHAN MUSKULOSKELETAL AKIBAT PENGGUNAAN LAPTOP PADA MAHASISWA FAKULTAS TEKNIK JURUSAN ARSITEKTUR UNIVERSITAS DIPONEGORO - Rakhmat Eddy Wicaksono; Suroto Suroto; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Musculoskeletal complaints are complaints on the part of skeletal muscles which felt by someone starting from very mild to very severe compaints. When the muscles receive static load repeatedly for a long time, it can cause damage to muscles, nerves tendons, joints, cartilages, and intervertebralis discus. There are several factors which cause Musculoskeletal disorders; such as occupational, individual, and environmental factors; and they have impacts on reduction of work productivity. The purpose of this study was to determine the relationship of postures, duration, and frequency of work with Musculoskeletal disorders due to laptop usage on college students in architecture departement of engineering, Diponegoro University. This type of research was explanatory research with cross sectional approach. The population which used in this study were 127 with a sample of 60 students. It analyzed by using univariate and bivariate with Chi-square test. The results showed almost all respondents had complained on Musculoskeletal disorders, which was 91,7 percent. The results of the bivariate analysis showed that there was a relationship between work postures (p-value 0,03) and duration of work (p-value 0,03) with Musculoskeletal disorders due to laptop usage on college students in architecture departement of engineering, Diponegoro University. There was no correlation between the frequency of work with Musculoskeletal disorders due to laptop usage on college students in architecture departement of engineering, Diponegoro University (p-value 0,0676). There was a relationship between two variables, which are work postures and work duration, with Musculoskeletal complaints. Researcher gave information of the correct postures and also the impacts of using laptop to college students in architecture departement of engineering, Diponegoro University, so they could avoid Musculoskeletal disorders due to laptop usage.